The resilience instrument for older adults: scale development and preliminary validation - Chun Hu; Chun-Qing Zhang; Jingdong Liu; Yiqun Gan (Cogent Psychology)
The aim of the current study was to develop and validate an age-specific resilience scale, the Resilience Instrument for Older Adults (RIOA), in a total sample of community-dwelling Chinese older adults (N = 470, with 112 males and 358 females) in Hong Kong, China. A sequential approach was used to develop the RIOA in three stages. In Study 1, scale candidate items were generated and initial content validity of the RIOA were explored. In Study 2, the factorial structure of the RIOA was extracted using exploratory factor analysis. In Study 3, exploratory structural equation modeling was conducted to test the structure. The reliability and validity of the RIOA were also examined. A pool of 70 candidate items for RIOA was established with good content validity in Study 1. In Study 2, seven factors were identified to construct resilience with 27 items: perseverance, self-reliance, spirituality, social support, living in the moment, environmental support, and meaningfulness, reflecting internal, external and existential dimensions. In Study 3, the RIOA demonstrated acceptable internal consistency (α = 0.87) and good criterion as well as construct validities, with 24 items finally confirmed. The measurement model also displayed satisfying model fit and was proven invariant across gender. This study provided a reliable and valid age-specific instrument for the measurement of resilience in older people. It is believed that this measure could be utilised in older adults who might benefit from exposure to resilience-based interventions geared toward strengthening quality of life.